When conduct achievement does (and does not) make you smile: it depends on your self-construal - Jacky C. K. Ng; Iris W. Y. Lai; Algae K. Y. Au; Joanne Y. H. Chong; Wesley C. H. Wu; Victor C. Y. Lau (International Journal of Adolescence and Youth)
A great deal of investigation has been devoted to studying whether academic achievement is linked to adolescents’ life satisfaction, whereas limited studies have focused on conduct achievement, which serves as another common kind of achievement in school. To examine the association between conduct achievement and life satisfaction, two studies were conducted using a mixed-methods sequential explanatory design with a two-phase model. Study 1 (quantitative phase) demonstrated longitudinal evidence for the positive effect of conduct achievement on adolescents’ life satisfaction. Critically, the lagged effect was also moderated by interdependent self-construal, with the beneficial effect becoming stronger for adolescents high in interdependent self-construal. Study 2 (qualitative phase) generated two main themes and four subthemes to understand the meaning and impact of conduct achievement to adolescents. Thematic analysis revealed that conduct achievement was regarded as a partial and subjective assessment by teachers and might elicit a positive perception of the teacher-student relationship.